Palynological records and paleoclimatic significance during the middle and late Late Pleistocene in the Qingshuihe Basin, Ningxia - WEI Lijie; LI Zhenhong; LI Mingtao; DONG Xiaopeng; CUI Jiawei; KOU Linlin (Dizhi lixue xuebao, 2023)
Desertification and drought in inland Asia are closely related to human habitation and social sustainability in western China. The climate in western China has experienced multiple shifts in temperature and aridity since the Late Pleistocene. Investigating this region's Late Pleistocene paleoclimatic changes contributes to predicting future climate trends. This study analyzes the pollen records from the Qingshuihe Basin in southern Ningxia during the middle to late Late Pleistocene, revealing four distinct pollen assemblage zones from bottom to top. These zones reflect paleovegetation and paleoclimate changes during the middle to late Late Pleistocene. The results indicate that during the middle Late Pleistocene (75-50 ka B.P.), the region featured a predominantly Artemisia-dominated steppe landscape with a cool and relatively dry climate. In the late Late Pleistocene (25-15 ka B.P.), the area experienced alternations between desert-steppe or steppe and forest-steppe, transitioning gradually to desert-steppe. During this period, the winter monsoon strengthened, leading to progressively cooler and drier conditions, with the climate shifting from cool and slightly moist to cold and arid. The further study of the palynological records during the middle and late Late Pleistocene in the Qingshuihe Basin of southern Ningxia holds significant implications for a proper understanding of the natural environmental history of the Loess Plateau and informs decision-making for its management.